The impact of accounting standards convergence on Chinese firms' overseas mergers and acquisitions - Shuwei Sun; Hailong Zhao; Xianjie He; Ying Zhang (China Journal of Accounting Research, 2019)
This paper investigates how accounting standards (AS) convergence influences Chinese firms' overseas mergers and acquisitions (M&As) and shows that this convergence significantly promotes Chinese firms' overseas M&As. Specifically, we find that both the probability of success and the value of transactions increases significantly in countries that implemented International Financial Reporting Standards (IFRS) prior to 2007. These results suggest that accounting standards (AS) convergence can improve the comparability of accounting information between China and other countries that have adopted IFRS. Moreover, we find that the impact of accounting standards (AS) convergence on state-owned enterprise (SOE) acquirers is weak. These findings demonstrate that accounting standards (AS) convergence can facilitate Chinese firms' overseas M&As by improving the comparability of accounting information between China and target countries.
Keywords: 650; Accounting standards convergence; Comparability of accounting information; Overseas mergers and acquisitions